Plastic bag usage in a taxed environment Investigation on the deterrent nature of plastic levy in Maun, Botswana - Mogomotsi, Patricia K (Waste management & research : the journal of the International Solid Wastes and Public Cleansing Association, ISWA, 2019)
Following the discovery of diamonds in Botswana, there was widespread use of plastic bags, possibly as a positive reaction to the change in economic and financial landscape of the country. The excessive use of plastic bags by consumers throughout Botswana, however, imposed several negative externalities to the environment and consequently to livelihoods through their effects on wildlife and livestock. The government of Botswana, in an effort to mitigate the negative impacts of plastic bags on the environment, introduced both a ban of plastics with less than minimum thickness and a plastic bag levy. This study assesses if the plastic bag levy regulation by the government is achieving its goal of reducing the use of plastic bags in Botswana, where Maun is used as a case study. It analyses consumers' perceptions about the plastic levy and its effects on their consumption. A total of 154 semi-structured questionnaires were administered through random selections of respondents at two shopping malls in Maun. In conclusion, the study established that although the levy is well targeted on consumers as sources of plastic bag litter, the levy is yet to attain its intended purpose of effecting a reduction of plastic bags demanded and/or consumed in Maun